Multiple endocrine neoplasia. - Thakker, R (2001)
Multiple endocrine neoplasia (MEN) is characterized by the occurrence of tumours involving two or more endocrine glands; two major forms, referred to as MEN1 and MEN2, are recognized. MEN1 is characterized by parathyroid, pancreatic islet and anterior pituitary tumours, whilst MEN2 is characterized by medullary thyroid carcinoma (MTC) in association with phaeochromocytoma. There are three clinical variants, referred to as MEN2A, MEN2B and MTC-only. All these forms of MEN may be inherited as autosomal dominant syndromes. The MEN1 gene is on chromosome 11q13 and about 300 MEN1 mutations have been identified. These are of diverse types and are scattered throughout the coding region. There is also a lack of genotype-phenotype correlation. All these findings make it difficult to implement MEN1 mutational analysis in the clinical setting. The situation in MEN2 is more straightforward. The gene causing all three MEN2 variants is located on chromosome 10cen-10q11.2, and is the c-ret proto-oncogene which encodes a tyrosine kinase receptor with cadherin-like and cysteine-rich extracellular domains, and a tyrosine kinase intracellular domain. Specific mutations of c-ret have been identified for each of the three MEN2 variants and mutational analysis has been used in the diagnosis and management of patients and families with the MEN2 variants.